PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS TEKNOLOGI AUGMENTED REALITY PADA DIMENSI TIGA DI SMK NEGERI 11 MALANG - Bellariksa Suliyono; Yuniar Ika Putri Pranyata; Timbul Yuwono (De Fermat : Jurnal Pendidikan Matematika, 2022)
This study uses the ADDIE Model development model through 5 stages: Analysis, Design, Development, Implementation and Evaluation. This study aims to produce learning media that meet the criteria of valid, effective, and practical. At SMK Negeri 11 Malang, the majority of IT majors, so for the learning model, you can use PjBL (Project Based Learning). Learning media can use augmented reality-based applications. This media received very valid criteria with a percentage of 3.8 from design experts, 3.7 from material experts, 3.3 from learning experts. The average validity test result is 3.6 in the conclusion that this media is very valid. The quality of the media produced met the criteria of being very practical with a percentage of 3.58 in the small group test and the large group test of 3.62. The average practicality test result is 3.6 concluded that this medium is very practical. The results of the effectiveness trial with the percentage of student completion scores during small group trials and large group trials were 100%. Based on these results, it can be concluded that the augmented reality-based media developed is valid, practical, and effectively used in learning three-dimensional material at SMK Negeri 11 Malang.